The Role of Large-Scale Data Infrastructure in Developing Next-Generation Deep Brain Stimulation Therapies - Chen, Witney; Kirkby, Lowry; Kotzev, Miro; Song, Patrick; Gilron, Ro’ee; Pepin, Brian (Frontiers in Human Neuroscience, 2021)
Advances in neuromodulation technologies hold the promise of treating a patient’s unique brain network pathology using personalized stimulation patterns. In service of these goals, neuromodulation clinical trials using sensing-enabled devices are routinely generating large multi-modal datasets. However, with the expansion of data acquisition also comes an increasing difficulty to store, manage, and analyze the associated datasets, which integrate complex neural and wearable time-series data with dynamic assessments of patients’ symptomatic state. Here, we discuss a scalable cloud-based data platform that enables ingestion, aggregation, storage, query, and analysis of multi-modal neurotechnology datasets. This large-scale data infrastructure will accelerate translational neuromodulation research and enable the development and delivery of next-generation deep brain stimulation therapies.